'We Cross Examine with Old Sonic DNA': King Britt and Tara Rodgers in conversation on Blacktronika, music technology and pedagogy. Issue 1 (April 2022) - Britt, King; Rodgers, Tara
Abstract : Composers, producers and educators King Britt and Tara Rodgers discuss music technology history and pedagogy in the context of King Britt's Blacktronika course at the University of California San Diego, which researches and celebrates Black artists and other artists of colour who are pioneers of electronic music genres. Conducted over email in June 2021, this interview also touches on King Britt's studio practice and evolution as an artist and educator, as well as on the social and political roots of contemporary electronic music genres.